Typeface sebagai Elemen Visual Pendukung City Branding di Kota Bukittinggi - Abdah Shalihah; Hendara Afriwan (GLOBAL SCIENTS PUBLISHER, 2026)
Bukittinggi City is a tourist and cultural hub in West Sumatra Province, boasting a strong identity through physical icons such as the Jam Gadang Clock Tower. However, Bukittinggi's visual identity in public spaces, particularly on signage, is still dominated by generic typefaces that fail to reflect local cultural character. This research aims to design a distinctive typeface for Bukittinggi City, inspired by a stylization of the traditional Minangkabau Saluak Laka motif. This motif was chosen because of its philosophical alignment with the Carano element of Bukittinggi's official emblem and the motto